The influence factors of mother in using postpartum contraceptives : - Rokhana Purwanti; Idi Setiyobroto; Yuliantisari Retnaningsih (Jurnal Kesehatan Ibu dan Anak, 2022)
The main problem of the population in Indonesia is the large population with a fairly high population growth rate of 1.49% per year, so it is necessary to increase the Family Planning program. This research is expected to be useful as a learning material in adding knowledge about postpartum Family Planning and the factors that influence it, so that postpartum mothers get consideration for participating in using postpartum contraceptives. This study aims to analyze the factors that influence mothers in using postpartum contraceptives. This research method was quantitative with case control design. The study population was all puerperal mothers in 2021 with quota sampling techniques in the work area of Kokap I Public Health Center, Kulon Progo, Yogyakarta. The subjects of this study were 33 mothers who used postpartum contraceptives and 33 mothers who didn’t use postpartum contraceptives. The results showed p<0.05 are parity, motivation and husband support had an influence on postpartum contraceptives use. Multivariate analysis of logistic regression showed motivation (OR=4,825), parity (OR=3,638) and husband support (OR=2,407). The motivation variable is the variable that most affects the use of postpartum contraceptives. Factors that influence mothers in using postpartum contraceptives are motivation, parity, and husband support. The biggest influence factor is motivation.